A Meta-Analysis of the Willingness to Pay for Reductions in Pesticide Risk Exposure - Chiara M. Travisi; Peter Nijkamp; Raymond J. G. M. Florax (Fondazione Eni Enrico Mattei (FEEM), 2004)
The use of environmental policy instruments such as eco-labelling and pesticide taxes should preferably be based on disaggregate estimates of the individuals' willingness to pay (WTP) for pesticide risk reductions. We review the empirical valuation literature dealing with pesticide risk exposure and develop a taxonomy of environmental and human health risks associated with pesticide usage. Subsequently, we use meta-analysis to investigate the variation in WTP estimates for reduced pesticide risk exposure. Our findings show that the WTP for reduced risk exposure is approximately 15% greater for medium, and 80% greater for high risk-levels, as compared to low risk levels. The income elasticity of pesticide risk exposure is generally positive, although not overly robust. Most results indicate that the demand for human health and environmental safety is highly elastic. We also show that geographical differences, characteristics of the survey, and the type safety device (eco-labelling, integrated management, or bans) are important drivers of the valuation results.
Keywords: D18; H23; I12; Q25; 330; Pesticide risk; Willingness to pay; Meta-analysis; Zahlungsbereitschaftsanalyse; Pestizid; Umweltbelastung; Schätzung; USA